Sugarcane Mosaic - Philippe Rott; Jack C. Comstock; Robert A. Gilbert; Hardev Sandhu (EDIS, 2015)
Mosaic’s most distinctive symptom is a pattern of contrasting shades of green, often islands of normal green on a background of paler green or yellowish chlorotic areas on the leaf blade. It had not been a problem in Florida until 1996, when it was observed on CP72-2086, a major commercial cultivar, near the intersection of Hatton Highway and US 98. Presently, because of the limited acreage of CP72-2086, the disease is only a potential threat. This revised 3-page fact sheet was written by P. Rott, J. C. Comstock, R. A. Gilbert, and H. S. Sandhu, and published by the UF Department of Agronomy, March 2015. (Photo: Philippe Rott, UF/IFAS)